Inovasi Pemasaran dan Pemanfaatan Potensi Profitabilitas pada Minuman Fermentasi Tepache - Elly Rasmikayati; Eti Suminartika; Bobby Rachmat Saefudin (Politeknik Piksi Ganesha Indonesia, 2025)
The food and beverage industry contributes significantly to the Indonesian economy. The fermented beverage market is growing due to consumer awareness of health. Recently, there has been a development in non-dairy fermented products, one example of a popular fermented drink is tepache. Tepache fermented drinks have the potential to become a business because in addition to utilizing waste, Indonesia also has the potential for local fruit. By applying production skills, packaging and storage technology, business management, and good marketing will support business potential. This community service program seeks to advocate marketing innovation and business opportunities. Because there are still obstacles, the product packaging currently used is less attractive to customers and there are still many prospective buyers who do not know the products and businesses of the Al-Qur'an garden due to the lack of information dissemination. The method used is Focus Group Discussion (FGD) for advocacy of marketing innovation and calculation of Production Cost for advocacy of business opportunities. The results obtained are packaging using cans that can maintain the quality and integrity of the product and informative packaging design to provide information effectively to customers and promotion through social media. In addition, tepache fermented drinks have promising business opportunities because the market is still open and the price range is in accordance with the health benefits offered by tepache fermented drinks.